Detection of testosterone based on the interaction between variable regions of antibody heavy chain and light chain - Zhao, Guangwei; Zhang, Shengshuo; Zou, Yujie; Jia, Nan; Zheng, Liyuan; Dong, Jinhua (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionTestosterone is a steroid hormone, which plays a pivotal role in regulating metabolism and protein synthesis in the body. The detection of testosterone is of paramount importance for diagnostic purposes in clinical settings, as well as for monitoring athletes’ physiological parameters and ensuring the integrity of sports competitions.MethodsHerein, we present a phage display-derived biosensing platform through genetic engineering of the TS77 antibody variable domains. The variable region genes of the heavy and light chains from TS77 antibody were cloned into the pDong1 plasmid and displayed on the phage surfaces through phage display technology. Subsequently, a novel non-competitive open-sandwich ELISA (OS-ELISA) was developed for testosterone detection, leveraging the antigen-induced interaction changes in antibody variable regions.ResultsOS-ELISA based on anti L-chain antibody achieved a limit of detection (LOD) of 2.71 nM and a half-maximal effective concentration (EC50) of 0.22 μM for testosterone detection. Furthermore, the enhanced OS-ELISA platform incorporating purified maltose binding protein fused with VL (MBP-VL) and VH phage demonstrated a LOD of 1.07 pM and a wide working range from 1 pM to 10 mM.DiscussionThe OS-ELISA developed in this study exhibits high sensitivity and a broad dynamic range for testosterone quantification, showing significant potential for clinical diagnostics and athlete monitoring applications.